Sealant for display element, cured product thereof, and display device

The sealant composition for organic EL display devices, incorporating cationic polymerizable compounds and a leveling agent, addresses the issue of storage stability and inkjet coating variability, enhancing the reliability and manufacturing stability of organic EL display devices.

JP7667855B2Active Publication Date: 2025-04-23MITSUI CHEMICALS INC
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2023520978
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-05-11
Filing Date
2022-04-28
Publication Date
2025-04-23
Estimated Expiration
2042-04-28

AI Technical Summary

Technical Problem

Existing sealants for organic EL display devices lack sufficient storage stability, leading to fluctuations in viscosity and curing properties due to temperature changes during storage, which results in adhesion issues with the inkjet head and decreased yield.

Method used

A sealant composition containing cationic polymerizable compounds, a cationic polymerization initiator, and a leveling agent, with a droplet diameter ratio R of 0.5 or more and 1.1 or less, providing enhanced storage stability and improved inkjet coating properties.

Benefits of technology

The proposed sealant achieves high storage stability, minimizing variations in inkjet coating properties and the performance of the cured product, thereby improving the reliability and manufacturing stability of organic EL display devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007667855000011
    Figure 0007667855000011
  • Figure 0007667855000001
    Figure 0007667855000001
  • Figure 0007667855000002
    Figure 0007667855000002
Patent Text Reader

Abstract

Provided is a sealant for a display element, the sealant containing (A) a cationically polymerizable compound, (B) a cationic polymerization initiator, and (C) a levelling agent, wherein the drop diameter ratio R of the sealant for a display element, before and after refrigeration for seven days at 5℃, is 0.5 to 1.1.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a sealant for a display element, a cured product thereof, and a display device. [Background technology]

[0002] In the field of display devices, efforts are being made to improve the properties of encapsulants. Hereinafter, an organic electroluminescence (EL) display device will be described as an example.

[0003] Organic EL elements are becoming increasingly used in displays and lighting devices because of their low power consumption. Organic EL elements are susceptible to deterioration due to moisture and oxygen in the atmosphere, so they are sealed with various sealing materials before use. Various materials have been considered for use in this sealing.

[0004] As a method for applying a sealant for an organic EL display element, an inkjet method is preferably used, and a sealant for an organic EL display element for inkjet application is required to have a high level of storage stability. The reasons are as follows.

[0005] When applying a sealant for display elements by the inkjet method, the sealant is first introduced into an inkjet cartridge, and then the inkjet cartridge is set in an inkjet device, and the sealant for display elements is applied to an object by inkjet coating. Here, due to the convenience of the manufacturing process, the sealant may be stored in the cartridge for a long period of time, from several days to several months. During this period, the environmental temperature may change, and the ink cartridge may be subjected to temperature history during inkjet coating.

[0006] If the viscosity and curing properties of the sealant change due to long-term storage or temperature history during storage, the sealant may adhere to the inkjet head or the curing behavior after landing may vary, resulting in a decrease in yield. For these reasons, storage stability of the sealant is required. As conventional techniques for improving the storage stability of such sealants, the techniques described in Patent Documents 1 and 2 are known.

[0007] Patent Document 1 describes a method for producing a coating film containing a photopolymerizable compound and a photopolymerization initiator, in which light with a peak wavelength of 395 nm is applied to a coating film having a thickness of 10 μm under an atmospheric condition at room temperature and normal pressure with an integrated light quantity of 800 mJ / cm. 2 More than 4000mJ / cm 2 An ultraviolet-curable resin composition is described, in which the DSC curve of a photocured product obtained by irradiating under the following conditions has a peak within the range of 30°C to 260°C (Claim 1).

[0008] In Patent Document 2, a coating film of a 10 μm-thick ultraviolet-curable resin composition is irradiated with ultraviolet light having a peak wavelength of 395 nm at an integrated light dose of 800 mJ / cm 2 More than 4000mJ / cm 2 When irradiated within the following range, the UV irradiation intensity is 1W / cm 2 The following describes an ultraviolet-curable resin composition in which the reaction rate of the polymerizable compound in the coating film is less than 70% (claim 1). [Prior art documents] [Patent documents]

[0009] [Patent Document 1] JP 2020-105482 A [Patent Document 2] JP 2020-105483 A Summary of the Invention [Problem to be solved by the invention]

[0010] However, when the present inventors have examined the techniques described in the above patent documents, it has been found that it is difficult to obtain a sufficiently high level of storage stability with the techniques of Patent Document 1 and Patent Document 2. In these techniques, as described in the examples, storage stability is evaluated based on whether or not it can be continuously discharged for 10 minutes. If it can be continuously discharged for 10 minutes without any problems, it is judged to have good storage stability, and if the ink (composition) adheres to the inkjet head, it is judged to have poor storage stability (paragraph 0283 of Patent Document 1, paragraph 0219 of Patent Document 2). It is considered that the storage stability judged by such criteria can be improved even with the techniques of Patent Documents 1 and 2. However, in recent years, there has been a demand for higher performance than ever before for sealants, sealing films obtained by sealants, and ultimately organic EL elements, as well as a demand for minimizing variation. In order to meet such demands, it is not enough to simply suppress the adhesion of the ink (composition) to the inkjet head, and a higher level of stability of the sealant is required.

[0011] In recent years, a method of incorporating a leveling agent is often used to further improve the performance of an encapsulating resin composition. The present inventors have found that when an encapsulating resin composition containing such a leveling agent is used, there is a problem that has not been recognized in the past. That is, the performance of the encapsulating resin composition changes slightly during transportation, which causes fluctuations in inkjet coating characteristics and the performance of the obtained cured product.

[0012] In view of the above, the present invention provides a high level of storage stability to a sealant for display elements, particularly to a sealant resin composition containing a leveling agent. [Means for solving the problem]

[0013] According to the present invention, there are provided a sealant for a display element, a cured product, and a display device as described below. [1] The following ingredients (A) to (C): (A) a cationically polymerizable compound, (B) a cationic polymerization initiator, (C) Leveling agent A sealant for a display element comprising: The droplet size ratio R of the sealant for display elements is 0.5 or more and 1.1 or less, as measured by the following measurement procedure: Sealant for display elements. [Measurement procedure] (i) After the display element sealant is brought to a state of 23° C., a portion of the display element sealant is sampled and ink-jet coated onto a SiN substrate under the following conditions. (a) Discharge volume: 7 picoliters (b) Temperature of SiN substrate and ambient temperature: 23°C After 180 seconds have elapsed since the droplets landed, the diameter of the droplets of the sealant for display elements is measured, and the measurement result is designated as D1. (ii) 9 to 11 g of the sealant for display elements kept at 23° C. in the above step (i) is introduced into a glass container having a volume of 19 mL, and the container lid is then closed. The container containing the sealant for display elements is refrigerated at 5° C. for 7 days. (iii) The sealant for a display element refrigerated in the step (ii) is collected, and the sealant for a display element is ink-jet coated onto a SiN substrate under the following conditions. (a) Discharge volume: 7 picoliters (b) Temperature of SiN substrate and ambient temperature: 23°C After 180 seconds have elapsed since the droplets landed, the diameter of the droplets of the sealant for display elements is measured, and the measurement result is designated as D2. (iv) From the above D1 and D2, the droplet size ratio R=D2 / D1 is calculated. [2] The sealant for a display element according to [1], The sealant for display elements, wherein the component (A) contains one or both of an epoxy compound and an oxetane compound. [3] The sealant for a display element according to [1] or [2], The sealant for display elements, wherein the component (C) is at least one member selected from the group consisting of silicone-based polymers and acrylate-based polymers. [4] The sealant for a display element according to any one of [1] to [3], The sealant for display elements, wherein the component (C) is a silicone-based polymer having a polymethylsiloxane structure or a polydimethylsiloxane structure in the molecule. [5] The sealant for a display element according to any one of [1] to [4], The sealant for a display element, wherein the component (C) is a polymer containing a structural unit derived from an alkyl (meth)acrylate ester. [6] The sealant for a display element according to any one of [1] to [5], The sealant for display elements, wherein the content of the component (C) is 0.01% by mass or more and 5% by mass or less relative to 100% by mass of the component (A). [7] The sealant for a display element according to any one of [1] to [6], The sealant for display elements, wherein the component (B) is a photocationic polymerization initiator that generates a cationic species that initiates polymerization by the action of light. [8] The sealant for a display element according to any one of [1] to [7], A sealant for display elements having a viscosity of 5 mPa·s or more and 80 mPa·s or less at 25°C and 20 rpm, as measured with an E-type viscometer. [9] The sealant for a display element according to any one of [1] to [8], A sealant for display elements, used to seal organic EL display elements.

[10] A cured product obtained by curing the sealant for a display element according to any one of [1] to [9].

[11] A substrate; A display element disposed on the substrate; A sealing layer that covers the display element; Including, A display device, wherein the sealing layer is formed from a cured product of the sealant for a display element according to any one of [1] to [9]. Effect of the Invention

[0014] According to the present invention, there is provided a sealant for a display element having a high level of storage stability. [Brief description of the drawings]

[0015] [Figure 1] 1 is a cross-sectional view showing a configuration example of an organic EL display device according to an embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0016] Hereinafter, an embodiment of the present invention will be described with reference to the drawings. In all drawings, similar components are given the same reference numerals, and the description will be omitted as appropriate. In this embodiment, each component may be used alone or in combination of two or more. In addition, the symbol "to" indicating a numerical range means greater than or equal to or less than, and includes both the upper limit and the lower limit. In addition, "(meth)acrylic acid" means acrylic acid or methacrylic acid.

[0017] (Sealant for display elements) In the present embodiment, the sealant for a display element (hereinafter, also simply referred to as "sealant") contains the following components (A) to (C). (A) Cationic polymerizable compound (B) Cationic polymerization initiator (C) Leveling agent The droplet size ratio R of the sealant for a display element, measured by the following measurement procedure, is 0.5 or more and 1.1 or less. [Measurement procedure] (i) After the display element sealant is brought to a state of 23° C., a portion of the display element sealant is sampled and ink-jet coated onto a SiN substrate under the following conditions. (a) Discharge volume: 7 picoliters (b) Temperature of SiN substrate and ambient temperature: 23°C After 180 seconds have elapsed since the droplets landed, the diameter of the droplets of the sealant for display elements is measured, and the measurement result is designated as D1. (ii) 9 to 11 g of the sealant for display elements kept at 23° C. in the above step (i) is introduced into a glass container having a volume of 19 mL, and the container lid is then closed. The container containing the sealant for display elements is refrigerated at 5° C. for 7 days. (iii) The sealant for a display element refrigerated in the above step (ii) is collected, and the sealant for a display element is ink-jet coated onto a SiN substrate under the following conditions. (a) Discharge volume: 7 picoliters (b) Temperature of SiN substrate and ambient temperature: 23°C After 180 seconds have elapsed since the droplets landed, the diameter of the droplets of the sealant for display elements is measured, and the measurement result is designated as D2. (iv) From the above D1 and D2, the droplet size ratio R=D2 / D1 is calculated.

[0018] The sealant has the above-mentioned configuration and thereby achieves a high level of storage stability. The sealant will now be described in detail. (Droplet diameter ratio R) The droplet size ratio R is measured by the measurement procedure consisting of the above-mentioned steps (i) to (iv). Each of the steps (i) to (iv) will be described in detail below.

[0019] Step (i) First, the prepared sealant for display elements is kept at 23°C, and then a portion of the sealant for display elements is taken and set in an inkjet device. For example, the sealant is introduced into an inkjet cartridge, and the cartridge is set in the inkjet device. The inkjet cartridge is heated so that the temperature of the sealant becomes, for example, 35°C. There is no limit to the warming time in the state where it is introduced into the inkjet cartridge, but it is preferably 1 minute to 24 hours.

[0020] Next, the inkjet cartridge containing the sealant for display elements is set in an inkjet device, and the sealant for display elements is applied to the SiN substrate by inkjet coating under the following conditions. (a) Discharge volume: 7 picoliters (b) Temperature of SiN substrate and ambient temperature: 23°C

[0021] As the inkjet cartridge, for example, DMC-11610 (manufactured by Fujifilm Dimatix) can be used, and as the inkjet device, for example, DMP-2831 (manufactured by Fujifilm Dimatix) can be used. After landing by inkjet coating, 180 seconds later, the diameter of the landing droplet of the sealant for display elements is measured. The diameter can be, for example, the average value of the maximum diameter and the minimum diameter. The measurement result is designated as D1.

[0022] Step (ii) Of the prepared sealant for display elements, 9 to 11 g is placed in a glass container with a volume of 19 mL, and then the container lid is closed. The container containing the sealant for display elements is refrigerated at 5°C for 7 days. The container lid is closed tightly with sealing tape. The upper space inside the container is left as air.

[0023] Step (iii) The above-mentioned refrigerated sealant for display elements is introduced into an inkjet cartridge at room temperature and kept at 23° C. The sealant for display elements before keeping is preferably returned to 23° C. There is no limit to the keeping time in the state introduced into the inkjet cartridge, but it is preferably from 1 minute to 24 hours. Next, the inkjet cartridge containing the sealant for display elements is set in an inkjet device, and the sealant for display elements is applied to the SiN substrate by inkjet coating under the following conditions. (a) Discharge volume: 7 picoliters (b) Temperature of SiN substrate and ambient temperature: 23°C After 180 seconds have passed since the droplets landed, the diameter of the droplets of the sealant for display elements is measured. The diameter can be, for example, the average value of the maximum diameter and the minimum diameter. The measurement result is designated as D2.

[0024] Step (iv) (iv) From the above D1 and D2, the droplet size ratio R=D2 / D1 is calculated.

[0025] The lower limit of the droplet size ratio R is 0.5 or more, preferably 0.7 or more, and more preferably 0.9 or more, and the upper limit of the droplet size ratio R is 1.1 or less, and preferably 1.0 or less. By setting the droplet size ratio R in this range, a high level of storage stability can be achieved in the sealant containing the leveling agent. Note that, in conventional sealants for display elements containing a leveling agent, the droplet size ratio R is generally 2.6 or more.

[0026] (Manufacturing considerations) In order to obtain a sealant having a droplet size ratio R in the above range, it is necessary to pay attention to, for example, the following points in the manufacturing process. To obtain a sealant, (A) a cationic polymerizable compound, (B) a cationic polymerization initiator, (C) a leveling agent, and a solvent and other additives as appropriate are mixed. Prior to this mixing, it is preferable to perform an operation of removing dissolved oxygen by applying ultrasonic waves to (A) the cationic polymerizable compound and the solvent and performing nitrogen bubbling. In addition, it is preferable to perform an operation of removing dissolved oxygen by performing nitrogen bubbling after mixing. As a process for realizing a droplet size ratio R in the above range, for example, performing such an operation is effective.

[0027] Next, the components of the sealant will be described with specific examples. (Component (A)) Component (A) is a cationic polymerizable compound. The cationic polymerizable compound is a compound that can undergo cationic polymerization by light or heat, and has one or more groups selected from an epoxy group, an oxetane ring-containing group, a vinyl ether group, and an episulfide group in the molecule.

[0028] From the viewpoint of improving the strength of the cured product, the content of component (A) in the sealant is preferably 70 mass % or more, more preferably 80 mass % or more, even more preferably 85 mass % or more, and still more preferably 90 mass % or more, based on the total composition of the sealant.

[0029] Furthermore, from the viewpoint of improving the weather resistance of the sealing material, the content of component (A) in the sealant is preferably 99.9 mass % or less, more preferably 99.5 mass % or less, and even more preferably 99 mass % or less, based on the total composition of the sealant.

[0030] From the viewpoint of improving the weather resistance of the sealing material, it is preferable that component (A) contains one or both of an epoxy compound and an oxetane compound. The total content of the epoxy compound and the oxetane compound is preferably 50 mass% or more, more preferably 70 mass% or more, and further preferably 90 mass% or more, and component (A) may contain one or both of an epoxy compound and an oxetane compound.

[0031] (Epoxy compounds) The epoxy compound is a compound having one or more epoxy groups in one molecule, and specific examples thereof include monoepoxy compounds, difunctional epoxy compounds, and trifunctional or higher epoxy compounds. Examples of the epoxy compound include the following EP1 to EP3.

[0032] EP1 EP1 is an alicyclic epoxy compound, which is a compound having at least one epoxycycloalkyl group or epoxycycloalkenyl group in the molecule, or a compound having at least one group in which at least one epoxy group is bonded to an alicyclic ring by a single bond in the molecule.

[0033] EP2 EP2 is a bisphenol type epoxy compound such as bisphenol A type epoxy, bisphenol F type epoxy, bisphenol S type epoxy, 2,2'-diallyl bisphenol A type epoxy, hydrogenated bisphenol type epoxy, or propylene oxide-added bisphenol A type epoxy.

[0034] EP3 EP3 is an epoxy compound other than EP1 and EP2, and examples thereof include resorcinol type epoxy, biphenyl type epoxy, sulfide type epoxy, diphenyl ether type epoxy, dicyclopentadiene type epoxy, naphthalene type epoxy, phenol novolac type epoxy, ortho-cresol novolac type epoxy, dicyclopentadiene novolac type epoxy, biphenyl novolac type epoxy, naphthalene phenol novolac type epoxy, glycidyl amine type epoxy, alkyl polyol type epoxy, rubber modified type epoxy, and glycidyl ester compounds. From the viewpoint of improving the weather resistance of the sealing material, the epoxy compound preferably contains an alicyclic epoxy compound (the above EP1).

[0035] The alicyclic epoxy compound may be a compound having one or more alicyclic hydrocarbon structures and one or more epoxy groups in the molecule. The alicyclic epoxy compound may have one or more epoxy groups in the molecule, but preferably has two or more epoxy groups from the viewpoint of enhancing the curing property of the sealant.

[0036] Examples of the alicyclic epoxy compound include a compound containing a cycloalkene oxide structure such as an epoxycyclohexane structure, and a compound in which an epoxy group is bonded to a cyclic aliphatic hydrocarbon directly or via a hydrocarbon group, etc. From the viewpoint of enhancing the curing property of the sealant, the alicyclic epoxy compound is preferably a compound having a cycloalkene oxide structure.

[0037] Here, the cycloalkene oxide structure is a structure obtained by epoxidizing a cycloalkene with an oxidizing agent such as a peroxide, and is an epoxy group composed of two adjacent carbon atoms and an oxygen atom that constitute an aliphatic ring. Examples of the cycloalkene oxide include cyclohexene oxide and cyclopentene oxide, and preferably cyclohexene oxide.

[0038] The number of cycloalkene oxide structures in one molecule of an alicyclic epoxy compound having a cycloalkene oxide structure may be 1 or 2 or more. From the viewpoint of improving the transparency, heat resistance, light resistance, etc. of the cured product, the number of cycloalkene oxide structures in one molecule is preferably 2 or more. An example of an alicyclic epoxy compound having a cycloalkene oxide structure is a compound represented by the following general formula (1).

[0039] [ka]

[0040] In general formula (1), X is a single bond or a divalent linking group. The linking group can be selected from, for example, a divalent hydrocarbon group, a carbonyl group, an ether group (ether bond), a thioether group (thioether bond), an ester group (ester bond), a carbonate group (carbonate bond), an amide group (amide bond), a group in which a plurality of these are linked together, or a group containing these. Examples of the divalent hydrocarbon group include an alkylene group having 1 to 18 carbon atoms and a divalent alicyclic hydrocarbon group.

[0041] Among these, specific examples of the alkylene group having 1 to 18 carbon atoms include a methylene group, a methylmethylene group, a dimethylmethylene group, an ethylene group, a propylene group, and a trimethylene group.

[0042] Specific examples of divalent alicyclic hydrocarbon groups include divalent cycloalkylene groups (including cycloalkylidene groups) such as a 1,2-cyclopentylene group, a 1,3-cyclopentylene group, a cyclopentylidene group, a 1,2-cyclohexylene group, a 1,3-cyclohexylene group, a 1,4-cyclohexylene group, and a cyclohexylidene group. From the viewpoint of improving curability, X is preferably a single bond or a linking group having an oxygen atom, and more preferably a single bond.

[0043] From a similar viewpoint, the linking group having an oxygen atom is preferably -CO- (carbonyl group), -O-CO-O- (carbonate group), -COO- (ester group), -O- (ether group), -CONH- (amide group), a group in which a plurality of these groups are linked together, or a group in which one or more of these groups are linked to one or more divalent hydrocarbon groups. Specific examples of the alicyclic epoxy compound represented by general formula (1) are shown below.

[0044] [ka]

[0045] [ka]

[0046] In the above formula, l represents an integer of 1 to 10, and m represents an integer of 1 to 30. R represents an alkylene group having 1 to 8 carbon atoms, and is preferably an alkylene group having 1 to 3 carbon atoms, such as a methylene group, an ethylene group, a propylene group, or an isopropylene group. In addition, n1 and n2 each independently represent an integer of 1 to 30.

[0047] Specific examples of commercially available alicyclic epoxy compounds having a cycloalkene oxide structure include Celloxide (CEL) 2021P, Celloxide 2000, Celloxide 2081, Celloxide 3000, Celloxide 8000, and Celloxide 8010 (all manufactured by Daicel Corporation).

[0048] Other preferred examples of epoxy compounds include aliphatic epoxy compounds such as bifunctional aliphatic epoxy compounds such as 1,6-hexanediol diglycidyl ether (e.g., Epogosey HD(D), manufactured by Yokkaichi Synthetic Co., Ltd.) and neopentyl glycol diglycidyl ether (e.g., SR-NPG, manufactured by Sakamoto Yakuhin Kogyo Co., Ltd.). From the viewpoint of improving the curing property of the sealing material, the epoxy resin preferably contains an alicyclic epoxy compound and an aliphatic epoxy compound.

[0049] From the viewpoint of improving curability, the content of the epoxy compound in the sealant is preferably 20% by mass or more, more preferably 30% by mass or more, and even more preferably 40% by mass or more, based on the total composition of the sealant.

[0050] Furthermore, from the viewpoint of improving the flexibility and adhesion of the cured product, the content of the epoxy compound in the sealant is preferably 80 mass % or less, more preferably 70 mass % or less, even more preferably 60 mass % or less, and even more preferably 50 mass % or less, based on the total composition of the sealant.

[0051] (Oxetane Compounds) The oxetane compound is a compound having one or more oxetanyl groups in one molecule, and specific examples thereof include monooxetane compounds, bifunctional oxetane compounds, and trifunctional or higher oxetane compounds.

[0052] From the viewpoint of improving the curability of the sealing material, the oxetane compound may be one or more compounds selected from the group consisting of the following general formula (2) and general formula (3).

[0053] [ka]

[0054] [ka]

[0055] In the general formulae (2) and (3), Y represents an oxygen atom, a sulfur atom, or a single bond, and is preferably an oxygen atom from the viewpoint of improving the weather resistance of the sealing material.

[0056] R in general formula (2) 1a and R in general formula (3) 1brespectively represent a fluorine atom, an alkyl group having 1 to 6 carbon atoms, a fluoroalkyl group having 1 to 6 carbon atoms, an allyl group, an aryl group having 6 to 18 carbon atoms, a furyl group, or an ethynyl group.

[0057] In addition, s in the general formula (2) and t in the general formula (3) each represent an integer of 1 or more and 5 or less. 1a or R 1b When a molecule contains a plurality of R, they may be the same or different. 1a R between each other or adjacent 1b They may form a ring structure.

[0058] In addition, in the general formula (2), R 2a represents a hydrogen atom, an alkyl group having 1 to 10 carbon atoms, an alkenyl group having 2 to 6 carbon atoms, an aralkyl group having 7 to 18 carbon atoms, an alkylcarbonyl group having 2 to 6 carbon atoms, an alkoxycarbonyl group having 2 to 6 carbon atoms, an N-alkylcarbamoyl group having 2 to 6 carbon atoms, or a (meth)acryloyl group.

[0059] On the other hand, in general formula (3), R 2b R represents a p-valent linking group. In general formula (3), p represents 2, 3 or 4, and is preferably 2. 2b Specifically, represents oxygen, a linear or branched alkylene group having 1 to 12 carbon atoms, a linear or branched poly(alkyleneoxy) group, an arylene group, a siloxane bond, or a combination thereof.

[0060] (Bifunctional oxetane compound) From the viewpoint of improving the curability of the cured product of the sealant, it is also preferable that the oxetane compound is a bifunctional oxetane compound represented by the following general formula (5) or (6).

[0061] [ka]

[0062] R in general formulas (5) and (6) 5R is a hydrogen atom, an alkyl group having 1 to 6 carbon atoms, an allyl group, an aryl group, an aralkyl group, a furyl group, or a thienyl group. 6 are each divalent organic residues.

[0063] Examples of the alkyl group having 1 to 6 carbon atoms include methyl, ethyl, propyl, butyl, pentyl, hexyl, and cyclohexyl groups. Examples of the aryl group include phenyl, naphthyl, tolyl, and xylyl groups. Examples of the aralkyl group include benzyl and phenethyl groups. Examples of the divalent organic residue include an alkylene group, a polyoxyalkylene group, a phenylene group, a xylylene group, and a structure represented by the following formula:

[0064] [ka]

[0065] R in the formula 3 is an oxygen atom, a sulfur atom, -CH2-, -NH-, -SO-, -SO2-, -C(CF3)2- or -C(CH3)2-. R 4 is an alkylene group or arylene group having 1 to 6 carbon atoms. Examples of the alkylene group include alkylene groups having 1 to 15 carbon atoms, such as a methylene group, an ethylene group, a propylene group, a butylene group, and a cyclohexylene group. The polyoxyalkylene group is preferably a polyoxyalkylene group having 4 to 30 carbon atoms, preferably 4 to 8 carbon atoms, and examples thereof include a polyoxyethylene group and a polyoxypropylene group.

[0066] From the viewpoint of improving the curability of the cured product of the sealant, the oxetane compound is preferably an oxetane compound represented by general formula (6). Examples of the compound represented by general formula (6) include 3-ethyl-3{[(3-ethyloxetan-3-yl)methoxy]methyl}oxetane, and examples of commercially available products thereof include ARONOXETANE OXT-221 (manufactured by Toagosei Co., Ltd.).

[0067] (Monofunctional oxetane compound) From the viewpoint of improving the curability of the cured product of the sealant, it is also preferable that the oxetane compound is a compound represented by the following general formula (4).

[0068] [ka]

[0069] In the general formula (4), Y is an oxygen atom or a sulfur atom. From the viewpoint of improving the weather resistance of the sealing material, Y is preferably an oxygen atom. 1c R represents a hydrogen atom, a fluorine atom, an alkyl group having 1 to 6 carbon atoms, a fluoroalkyl group having 1 to 6 carbon atoms, an aryl group having 6 to 18 carbon atoms, a furyl group, or a thienyl group. 1c From the viewpoint of improving the curability of the cured product of the sealant, is preferably an alkyl group having 1 to 6 carbon atoms.

[0070] R 2c R is a hydrogen atom, an alkyl group having 1 to 10 carbon atoms, an alkenyl group having 2 to 6 carbon atoms, an aralkyl group having 7 to 18 carbon atoms, an alkylcarbonyl group having 2 to 6 carbon atoms, an alkoxycarbonyl group having 2 to 6 carbon atoms, an N-alkylcarbamoyl group having 2 to 6 carbon atoms, or a (meth)acryloyl group. 2c From the viewpoint of improving the curability of the cured product of the sealant, is preferably an alkyl group having 1 to 10 carbon atoms.

[0071] Specific examples of the compound represented by the general formula (4) include 3-ethyl-3-hydroxymethyloxetane, 3-(meth)allyloxymethyl-3-ethyloxetane, (3-ethyl-3-oxetanylmethoxy)methylbenzene, 4-fluoro-[1-(3-ethyl-3-oxetanylmethoxy)methyl]benzene, 4-methoxy-[1-(3-ethyl-3-oxetanylmethoxy)methyl]benzene, [1-(3-ethyl-3-oxetanylmethoxy)ethyl]phenyl ether, isobutoxymethyl(3-ethyl-3-oxetanylmethyl) ethyl) ether, isobornyloxyethyl (3-ethyl-3-oxetanylmethyl) ether, isobornyl (3-ethyl-3-oxetanylmethyl) ether, 2-ethylhexyl (3-ethyl-3-oxetanylmethyl) ether, ethyl diethylene glycol (3-ethyl-3-oxetanylmethyl) ether, dicyclopentadiene (3-ethyl-3-oxetanylmethyl) ether, 3-methacryloxymethyl-3-ethyloxetane, and 3-ethyl-3-[(2-ethylhexyloxy)methyl]oxetane. From the viewpoint of improving the weather resistance of the sealing material, the compound represented by the general formula (4) is preferably 3-ethyl-3-[(2-ethylhexyloxy)methyl]oxetane.

[0072] From the viewpoint of improving the curability of the cured product of the sealant, the content of the oxetane compound in the sealant is preferably 20% by mass or more, more preferably 30% by mass or more, even more preferably 40% by mass or more, and even more preferably 50% by mass or more, based on the total composition of the sealant. Also, from the viewpoint of making the viscosity of the sealant preferable, the content of the oxetane compound in the sealant is preferably 80% by mass or less, more preferably 70% by mass or less, and even more preferably 60% by mass or less, based on the total composition of the sealant.

[0073] (Component (B)) Component (B) is a cationic polymerization initiator. Specific examples of the cationic polymerization initiator include one or more selected from the group consisting of photoradical initiators and thermal polymerization initiators. From the viewpoint of stably forming a cured product at low temperatures, component (B) preferably contains a photocationic polymerization initiator (UV radical initiator, UV cationic initiator) that generates radicals or ions when irradiated with light such as ultraviolet light. The photocationic polymerization initiator may be any compound that is capable of generating cationic species upon exposure to light, such as light irradiation, and initiating polymerization of component (A).

[0074] A specific example of the cationic photopolymerization initiator is a salt of an onium ion (onium salt) represented by the following general formula (7): Such an onium salt releases a Lewis acid by photoreaction. [R 12 a R 13 b R 14 c R 15 d W] v+ [MX v+u ] u- (7)

[0075] In the general formula (7), W represents S, Se, Te, P, As, Sb, Bi, O, I, Br, Cl, or N≡N. 12 , R 13 , R 14 and R 15 each independently represents an organic group, and a, b, c, and d each independently represent an integer of 0 to 3. In addition, "a+b+c+d" is equal to the valence of W.

[0076] In addition, in the general formula (7), M represents a halogenated complex [MX v+u ] represents the metal or metalloid constituting the central atom. Specific examples of M include B, P, As, Sb, Fe, Sn, Bi, Al, Ca, In, Ti, Zn, Sc, V, Cr, Mn, and Co. In the general formula (7), X represents a halogen atom such as F, Cl, or Br, u represents the net charge of the halogenated complex ion, and v represents the atomic valence of M.

[0077] Specific examples of the onium ion in the general formula (7) include diphenyliodonium, bis(4-methoxyphenyl)iodonium, 4-methylphenyl-4'-isopropylphenyliodonium, bis(4-methylphenyl)iodonium, bis(4-tert-butylphenyl)iodonium, bis(dodecylphenyl)iodonium, tolylcumyliodonium, triphenylsulfonium, diphenyl-4-thiophenoxyphenylsulfonium, bis[4-(diphenylsulfonio)-phenyl]sulfide, bis[4-(di(4-(2-hydroxyethyl)phenyl)sulfonio)-phenyl]sulfide, and η5-2,4-(cyclopentadienyl)[1,2,3,4,5,6-η-(methylethyl)benzene]-iron(1+).

[0078] Specific examples of the anion in the general formula (7) include tetrafluoroborate, tetrakis(pentafluorophenyl)borate, hexafluorophosphate, hexafluoroantimonate, hexafluoroarsenate, and hexachloroantimonate.

[0079] From the viewpoint of excellent safety to living organisms, the anion in general formula (7) is preferably one selected from the group consisting of tetrafluoroborate, tetrakis(pentafluorophenyl)borate, and hexafluorophosphate.

[0080] Examples of commercially available photocationic polymerization initiators represented by general formula (7) include Irgacure 250, Irgacure 270, Irgacure 290 (manufactured by BASF), CPI-100P, CPI-101A, CPI-200K, CPI-210S, CPI-310B, CPI-400PG (manufactured by San-Apro Ltd.), SP-150, SP-170, SP-171, SP-056, SP-066, SP-130, SP-140, SP-601, SP-606, SP-701 (manufactured by ADEKA Corporation), and PI-2074 (trade name, manufactured by Rhodia Corporation). Among these, from the viewpoint of improving curability, the photocationic initiator represented by general formula (7) is preferably one or more types selected from the group consisting of Irgacure270, Irgacure290, CPI-100P, CPI-101A, CPI-200K, CPI-210S, CPI-310B, CPI-400PG, SP-150, SP-170, SP-171, SP-056, SP-066, SP-601, SP-606, SP-701, and PI-2074.

[0081] From the viewpoint of improving curability, the content of component (B) in the sealant is preferably 0.1 mass % or more, more preferably 0.2 mass % or more, and even more preferably 0.3 mass % or more, based on the total composition of the sealant.

[0082] In addition, from the viewpoint of suppressing coloration of the sealant, the content of component (B) in the sealant is preferably 10 mass % or less, more preferably 5 mass % or less, even more preferably 3 mass % or less, and even more preferably 2 mass % or less, based on the total composition of the sealant.

[0083] (Component (C)) Component (C) is a leveling agent. The leveling agent is an additive that makes it easier for the sealant applied by inkjet to wet and spread on the surface of the object to be applied. The leveling agent improves the fluidity and defoaming properties of the sealant, and also plays a role in improving the smoothness of the sealant coating surface that is formed. Examples of the leveling agent include fluorine-based, acrylic, and siloxane-based polymers. Of these, in terms of their small surface modification effect, component (C) is preferably one or more selected from the group consisting of silicone-based polymers and acrylate (acrylic) polymers.

[0084] The silicone polymer is preferably a polymer having a polymethylsiloxane structure or a polydimethylsiloxane structure in the molecule. The number of repetitions of dimethylsiloxane is more preferably, for example, from 2 to 150. Examples of the silicone polymer include polydimethylsiloxane, polyether-modified polydimethylsiloxane, polyester-modified polydimethylsiloxane, polymethylalkylsiloxane, and aralkyl-modified polymethylalkylsiloxane.

[0085] Specifically, the acrylic polymer is a polymer containing a structural unit derived from an alkyl (meth)acrylate ester, that is, a polymer of a monomer containing an alkyl (meth)acrylate ester. The number of carbon atoms in the alkyl chain of the alkyl (meth)acrylate ester is preferably 4 or more, more preferably 6 or more. The upper limit of the number of carbon atoms in the alkyl chain of the alkyl acrylate ester is, for example, 12. Examples of the alkyl acrylate ester include butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, and a copolymer of butyl acrylate and 2-ethylhexyl acrylate. It is preferable that the acrylate polymer does not contain a fluorine atom. The alkyl (meth)acrylate ester may be one type or two or more types.

[0086] Examples of leveling agents include: BYK-310, BYK-310N, BYK-323, BYK-340, BYK-350 manufactured by BYK-Chemie Japan; Polyflow KL-100, Polyflow KL-700, Polyflow KL-850, Polyflow No. 90 manufactured by Kyoeisha Chemical Co., Ltd.; DIC F-552, F-553, F-554, F-556, F-557, F-559; Examples include Viscoat 13F manufactured by Osaka Organic Chemical Industry Co., Ltd.

[0087] The weight average molecular weight Mw of the polymer constituting the leveling agent is, for example, about 1,000 to 20,000, preferably 2,000 to 10,000. By setting the molecular weight to the above upper limit or less, it is possible to suppress bleeding of the leveling agent from the sealant cured product. By setting the molecular weight to the above lower limit or more, it is possible to improve the flowability and defoaming property of the sealant and to sufficiently improve the smoothness of the sealant coating surface to be formed. Here, the weight average molecular weight Mw of the polymer constituting the leveling agent is measured by gel permeation chromatography (GPC) based on a polystyrene standard substance.

[0088] The content of the leveling agent (C) is preferably 0.01% by mass or more, more preferably 0.05% by mass or more, and even more preferably 0.1% by mass or more, based on 100% by mass of the component (A). The content of the leveling agent (C) is preferably 5% by mass or less, more preferably 3% by mass or less, and even more preferably 1% by mass or less, based on 100% by mass of the component (A). By making the content equal to or less than the lower limit, the flowability and defoaming properties of the sealant can be improved, and the smoothness of the sealant coating surface formed can be sufficiently improved. By making the content equal to or more than the upper limit, bleeding of the leveling agent from the cured product of the sealant can be suppressed.

[0089] In the present embodiment, the sealant may contain components other than the components (A) to (C). Examples of the components other than the components (A) to (C) are given below. (Component (D)) Component (D) is one or more compounds selected from the group consisting of benzotriazole compounds, triazine compounds, monophenol compounds, bisphenol compounds, trisphenol compounds, phosphite compounds, and oxaphosphaphenanthrene oxide compounds. By further including component (D) in the sealant, the weather resistance of the sealing material can be further improved.

[0090] Specific examples of benzotriazole compounds include 2-(2-hydroxy-5-methylphenyl)benzotriazole. Specific examples of commercially available benzotriazole compounds include TinuvinP, Tinuvin234, Tinuvin234FF, Tinuvin326, Tinuvin326FL, Tinuvin329, Tinuvin329FL, Tinuvin360, Chimassorb81, Chimassorb81FL (manufactured by BASF), KEMISORB71, KEMISORB73, KEMISORB74, KEMISORB79, KEMISORB279 (manufactured by Chemipro Chemicals), JF-77, JF-79, JF-80, JF-83, and JF-832 (manufactured by Johoku Chemical Industry Co., Ltd.).

[0091] Specific examples of triazine compounds include 2,4-bis(2-hydroxy-4-butyloxyphenyl)-6-(2,4-bis-butyloxyphenyl)-1,3,5-triazine and 2-hydroxyphenyl-s-triazine. Specific examples of commercially available triazine compounds include Tinuvin 460, Tinuvin 1577ED, Tinuvin 1600 (manufactured by BASF), and KEMISORB102 (manufactured by Chemipro Chemicals).

[0092] Specific examples of monophenol compounds include benzenepropanoic acid, 3,5-bis(1,1-dimethylethyl)-4-hydroxy-C7-C9 side chain alkyl ester, and 2,6-di-t-butyl-p-cresol. Specific examples of commercially available monophenol compounds include Irganox 1135 (manufactured by BASF), KEMISORB112, KEMISORB113, KEMISORB114, and KEMINOX76 (manufactured by Chemipro Chemicals).

[0093] A specific example of the bisphenol compound is 2,2-methylenebis(4-methyl-6-t-butylphenol). A specific example of a commercially available bisphenol compound is KEMINOX9425 (manufactured by Chemipro Chemicals). A specific example of a trisphenol compound is 1,1,3-tris(2-methyl-4-hydroxy-5-t-butylphenyl)butane.

[0094] From the viewpoint of improving the weather resistance of the sealing material, component (D) preferably contains one or more compounds selected from the group consisting of benzotriazole compounds, triazine compounds, and monophenol compounds, and more preferably contains one or two compounds thereof.

[0095] From the viewpoint of improving the weather resistance of the sealing material, the content of component (D) in the sealant is preferably 0.001 mass % or more, more preferably 0.01 mass % or more, and even more preferably 0.1 mass % or more, based on the total composition of the sealant.

[0096] From the viewpoint of improving the curability of the sealing material, the content of component (D) in the sealant is preferably 10 mass % or less, more preferably 5 mass % or less, and even more preferably 2 mass % or less, based on the total composition of the sealant.

[0097] (Other Ingredients) In the present embodiment, the sealant may further contain other components in addition to those described above, provided that the effects of the present invention are not impaired. Examples of the other components include a tackifier, a filler, a curing accelerator, a plasticizer, a surfactant, a heat stabilizer, a flame retardant, an antistatic agent, a defoamer, a silane coupling agent, and an ultraviolet absorbing agent.

[0098] The curing property of the sealant can be further improved by including a photosensitizer in the sealant. Examples of the sensitizer include a cationic photosensitizer. The photosensitizer is preferably a compound that is excited by light having a wavelength of 350 nm to 450 nm, from the viewpoint of compatibility with wavelength-selective light sources such as UV-LED. Specific examples of such sensitizers include polynuclear aromatics such as pyrene, perylene, triphenylene, and anthracene; xanthenes such as fluorescein, eosin, erythrosine, rhodamine B, and rose bengal; xanthones such as xanthone, thioxanthone, dimethylthioxanthone, and diethylthioxanthone; cyanines such as thiacarbocyanine and oxacarbocyanine; merocyanines such as merocyanine and carbomerocyanine; rhodacyanines; oxonols; thiazines such as thionine, methylene blue, and toluidine blue; acridines such as acridine orange, chloroflavin, and acriflavine; acridones such as acridone and 10-butyl-2-chloroacridone; anthraquinones; squaliums; styryls; base styryls; and coumarins such as 7-diethylamino-4-methylcoumarin. Among these, the photosensitizer is preferably a polycyclic aromatic compound, an acridone compound, a coumarin compound or a base styryl compound, more preferably an anthracene compound, from the viewpoint of improving the curability of the encapsulating material.

[0099] From the viewpoint of obtaining better curability of the sealant, the content of the photosensitizer in the sealant is preferably 0.1 mass % or more, more preferably 0.2 mass % or more, and even more preferably 0.3 mass % or more, relative to 100 mass parts of component (A), and is preferably 3 mass % or less, more preferably 1.5 mass % or less, and even more preferably 1 mass % or less.

[0100] Furthermore, by including a coupling agent in the sealant, the adhesion between the sealing material and the material to be sealed can be further improved. An example of the coupling agent is a silane coupling agent. From the viewpoint of improving the adhesion between the sealing material and the material to be sealed, the silane coupling agent is preferably a silane coupling agent having a functional group common to the polymerizable functional group in component (A), or a silane coupling agent having a functional group capable of reacting with the polymerizable functional group in component (A). For example, when component (A) contains an epoxy compound, the coupling agent preferably contains one or more selected from the group consisting of a silane coupling agent having an epoxy group and a silane coupling agent having a functional group that reacts with the epoxy group (for example, an addition reaction).

[0101] Specific examples of the silane coupling agent having an epoxy group include γ-glycidoxypropyltrimethoxysilane and β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane.

[0102] Specific examples of the silane coupling agent having a functional group capable of reacting with an epoxy group include silane coupling agents containing an amino group such as a primary amino group or a secondary amino group; a carboxyl group; a methacryloyl group; an isocyanate group, and the like.

[0103] Specific examples of these silane coupling agents include N-2-(aminoethyl)-3-aminopropylmethyldimethoxysilane, N-2-(aminoethyl)-3-aminopropylmethyltrimethoxysilane, N-2-(aminoethyl)-3-aminopropylmethyltriethoxysilane, 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, 3-triethoxysilyl-N-(1,3-dimethyl-butylidene)propylamine, N-phenyl-3-aminopropyltrimethoxysilane or 3-(4-methylpiperazino)propyltrimethoxysilane, trimethoxysilylbenzoic acid, γ-methacryloxypropyltrimethoxysilane, and γ-isocyanatopropyltriethoxysilane.

[0104] The coupling agent may include other silane coupling agents than those mentioned above, such as vinyltriacetoxysilane and vinyltrimethoxysilane. The molecular weight of the coupling agent is preferably 80 to 800 from the viewpoint of improving the adhesion between the sealing material and the material to be sealed.

[0105] From the viewpoint of improving the adhesion between the sealing material and the material to be sealed, the content of the coupling agent in the sealant is preferably 0.5% by mass or more, more preferably 1% by mass or more, and even more preferably 1.5% by mass or more, relative to 100 parts by mass of component (A), and is preferably 5% by mass or less, more preferably 4% by mass or less, and is also preferably 3% by mass or less.

[0106] The sealing agent may contain a polymerization inhibitor.Specific examples of the polymerization inhibitor include 2,2,6,6-tetramethylpiperidine-1-oxyl (free radical), 4-hydroxy-2,2,6,6-tetramethylpiperidine-1-oxyl (free radical), 4-amino-2,2,6,6-tetramethylpiperidine-1-oxyl (free radical), 4-pertamide-2,2,6,6-tetramethylpiperidine-1-oxyl (free radical), 4-acetamide-2,2,6,6-tetramethylpiperidine-1-oxyl (free radical), 4-carboxy-2,2,6,6-tetramethylpiperidine-1-oxyl (free radical), 4-methoxy-2,2,6,6-tetramethylpiperidine-1-oxyl (free radical), and 4-oxo-2,2,6,6-tetramethylpiperidine-1-oxyl (free radical).

[0107] The content of the polymerization inhibitor in the sealant is preferably 0.001 mass % or more, more preferably 0.01 mass % or more, and even more preferably 0.005 mass % or more, based on the total composition of the sealant, from the viewpoint of improving plasma resistance and suppressing damage to an element to which the sealant is applied.

[0108] From the viewpoint of improving the curing property of the sealing material, the content of the polymerization inhibitor in the sealing agent is preferably 1 mass % or less, more preferably 0.75 mass % or less, and further preferably 0.5 mass % or less, based on the total composition of the sealing agent.

[0109] From the viewpoint of improving the weather resistance of the sealing material and being suitable for forming a cured material by a coating method such as an inkjet method, in this embodiment, the sealant preferably does not contain a solvent, or when the sealant contains a solvent, the content of the solvent is more than 0 mass%, preferably 0.05 mass% or less, and more preferably 0.03 mass% or less. A specific embodiment in which the sealant does not contain a solvent includes a sealant in which no solvent is intentionally blended when the sealant is prepared.

[0110] Next, the characteristics of the sealant will be described. The glass transition temperature (Tg) of the cured product of the sealing agent is 40° C. or higher, preferably 50° C. or higher, and more preferably 60° C. or higher, from the viewpoint of improving the heat resistance of the sealing material. From the viewpoint of improving flexibility, the Tg of the cured product of the sealant is less than 200° C., preferably 190° C. or less, and more preferably 180° C. or less. Here, the glass transition temperature (Tg) is measured by the following procedure.

[0111] The cured sealant was prepared by sandwiching the uncured sealant between polyethylene terephthalate (PET) films using a 100 μm thick Teflon® sheet as a mold and irradiating it with a UV-LED with a wavelength of 395 nm at an illumination intensity of 1000 mW / cm. 2 , cumulative light intensity 1500mJ / cm 2 The resulting composition is cured under the conditions described above. The resulting cured product was cut with a cutter into a size of 10 mm width x 40 mm length.

[0112] Then, using a dynamic viscoelasticity measuring device "DMS6100" (manufactured by Seiko Instruments Inc.), a frequency of 1 Hz is applied to the cut-out cured product in the air, and tan δ is measured while raising the temperature from room temperature to 250°C at a rate of 5°C / min. The temperature at the peak top of tan δ is taken as the Tg of the cured product.

[0113] In this embodiment, a sealant having a Tg within a specific range can be obtained, for example, by appropriately selecting the components contained in the sealant and the blending ratio thereof and adjusting the production conditions.

[0114] The properties of the sealant are not limited, but the sealant is preferably liquid from the viewpoint of improving the flexibility and plasma resistance of the sealing material, and from the viewpoint of suitability for forming a cured material by a coating method such as an inkjet method.

[0115] Moreover, from the viewpoint of stably forming the sealing material, the sealant is preferably one that can be applied, and more preferably one that can be applied by an inkjet method.

[0116] The viscosity of the sealant, measured using an E-type viscometer at 25°C and 20 rpm, is preferably 5 mPa s or more, more preferably 8 mPa s or more, and even more preferably 10 mPa s or more, from the viewpoint of improving inkjet dischargeability. From the viewpoint of improving the ink-jet ejection properties, the viscosity of the sealant is preferably 80 mPa·s or less, more preferably 50 mPa·s or less, and further preferably 30 mPa·s or less.

[0117] From the viewpoint of improving the inkjet dischargeability, the thixotropic index (TI value) of the sealant is preferably 0.8 or more, more preferably 0.9 or more, and is preferably 1.1 or less, more preferably 1.0 or less. Here, the TI value is calculated by measuring the viscosity at 25° C. and rotation speeds of 5 rpm and 50 rpm using an E-type viscometer and then calculating it according to the following formula. TI value = (viscosity at 5 rpm) ÷ (viscosity at 50 rpm)

[0118] From the viewpoint of improving the sealing properties of the sealant, the dielectric constant of the cured product of the sealant is preferably 4.0 or less, more preferably 3.8 or less, and further preferably 3.6 or less. The dielectric constant of the cured product of the sealant can be, for example, 1.0 or more.

[0119] Here, the dielectric constant of the cured sealant is 1000mW / cm irradiance with a UV-LED of 395nm wavelength. 2 , cumulative light intensity 1500mJ / cm 2 The dielectric constant is measured at a frequency of 100 kHz for a cured product obtained by curing the curable composition under the above conditions.

[0120] Next, a method for producing the sealant will be described. The method for producing the sealing agent is not limited, and includes, for example, mixing the components (A) to (C) and other components as appropriate, such as various additives added as necessary. Examples of the method for mixing the components include a method in which the components are uniformly kneaded at room temperature or under heating, under normal pressure, reduced pressure, under pressure, or under an inert gas flow using various known kneading machines, such as a planetary stirring device, a homodisper, a universal mixer, a Banbury mixer, a kneader, a two-roll machine, a three-roll machine, or an extruder, either alone or in combination.

[0121] The obtained sealant can also be used to form a sealing material. For example, the sealant can be applied to a substrate and dried. For application, known techniques such as inkjet printing, screen printing, and dispenser application can be used. For drying, the sealant can be heated to a temperature at which component (A) does not polymerize. There is no limitation on the shape of the obtained sealing material, and it can be, for example, a film or layer.

[0122] As described in the section (Notes on manufacturing), in order to obtain a sealant having a specific droplet size ratio R, it is preferable to carry out an operation to remove dissolved oxygen in the manufacturing process, for example, by applying ultrasonic waves to (A) the cationic polymerizable compound and the solvent and by bubbling with nitrogen. In addition, it is preferable to carry out an operation to remove dissolved oxygen after mixing by bubbling with nitrogen. The sealing material is, for example, a cured product obtained by curing the sealant in this embodiment, and more specifically, a photocured product of the sealant.

[0123] Examples of methods for photocuring the sealant include methods of curing the sealant by irradiating it with light using a light source such as a low-pressure mercury lamp, a medium-pressure mercury lamp, a high-pressure mercury lamp, an ultra-high-pressure mercury lamp, an excimer laser, a chemical lamp, a black light lamp, a microwave-excited mercury lamp, a metal halide lamp, a sodium lamp, a halogen lamp, a xenon lamp, an LED lamp, a fluorescent lamp, sunlight, or an electron beam irradiation device.

[0124] In the present embodiment, the sealant contains a combination of the components (A) to (C) and has a droplet size ratio R within a specific range. Therefore, by using such a sealant, a high level of storage stability can be achieved.

[0125] In addition, the sealant obtained in this embodiment is suitable for use in sealing, for example, display elements, preferably organic EL display elements. According to this embodiment, a sealant that realizes a high level of storage stability can be obtained, and therefore the reliability of the sealing film and display device obtained from such a sealant can be improved. Damage to the display element during the manufacturing process of the display device can be effectively suppressed, and the manufacturing stability of the display device can also be improved.

[0126] By using the cured product of the sealant obtained in this embodiment as a sealant material for a display element, preferably an organic EL display element, a display device having excellent weather resistance can be obtained. Below, an example of the configuration of a display device will be given, taking an organic EL display device as an example.

[0127] (Organic EL display device) In this embodiment, the organic EL display device has a layer formed of a cured product of a sealant. Fig. 1 is a cross-sectional view showing an example of the configuration of an organic EL display device in this embodiment. The display device 100 shown in Fig. 1 is an organic EL display device, and includes a substrate (base layer 50), an organic EL element (light-emitting element 10) disposed on the base layer 50, and a sealing layer 22 (which may be an overcoat layer 22 or a barrier layer 22) that covers the light-emitting element 10. For example, the sealing layer 22 is made of a cured product of the sealant in this embodiment.

[0128] 1, the display device 100 has a barrier layer 21 (which may be a touch panel layer 21 or a surface protective layer 21), a sealing layer 22 (which may be an overcoat layer 22 or a barrier layer 22), a planarization layer 23 (which may be a sealing layer 23), and a barrier layer 24 as layers located closer to the observation side than the light-emitting element 10. The planarization layer 23 is provided on the base layer 50 so as to cover the light-emitting element 10, and the barrier layer 24 is provided on the surface of the planarization layer 23. The sealing layer 22 is provided on the base layer 50 so as to cover the planarization layer 23 and the barrier layer 24. In addition, the barrier layer 21 is provided on the sealing layer 22.

[0129] The specific configuration of each layer is not limited, and an appropriate configuration can be adopted based on generally known information. Moreover, such a display device 100 can be manufactured based on generally known information. By protecting the organic EL element with a resin layer obtained by curing the sealant of this embodiment, it is possible to sufficiently prevent moisture from penetrating into the organic EL element, thereby maintaining high performance and durability of the organic EL element. The organic EL display device may be of a top emission structure or a bottom emission structure. It is preferable that the organic EL element is disposed on a substrate and is previously covered with an inorganic material film so as to cover the region including the organic EL element before being protected by the resin layer obtained by curing the sealant in this embodiment.

[0130] The material of the base layer 50 is not limited, and various materials can be used, such as a glass substrate, a silicon substrate, a plastic substrate, etc. A TFT substrate having a plurality of TFTs (thin film transistors) and a planarization layer on a substrate can also be used.

[0131] The barrier layer 24, i.e., the inorganic material constituting the inorganic material film, is, for example, silicon nitride (SiN x ), silicon oxide (SiO x ), aluminum oxide (Al2O3), etc. The inorganic material film may be a single layer or a laminate of multiple types of layers.

[0132] Methods for covering the light emitting element 10 with an inorganic material film include, for example, sputtering and electron cyclotron resonance (ECR) plasma CVD when the inorganic material film is made of silicon nitride or silicon oxide.

[0133] Among these, the sputtering method can be carried out, for example, using a single or mixed gas such as argon or nitrogen as a carrier gas under conditions of room temperature, power of 50 to 1000 W, and pressure of 0.001 to 0.1 Torr.

[0134] The ECR plasma CVD method can be carried out using, for example, a mixed gas of SiH4 and O2 or a mixed gas of SiH4 and N2 under conditions of a temperature of 30° C. to 100° C., a pressure of 10 mTorr to 1 Torr, a frequency of 2.45 GHz, and a power of 10 to 1000 W.

[0135] Examples of a method for protecting the light emitting element 10 with a resin layer obtained by curing the sealant of this embodiment, such as the sealing layer 22, include a method of applying the sealant onto the light emitting element 10 and curing it. As a method for applying the sealant, it is preferable to use an inkjet method. The thickness of the resin layer is not limited, but from the viewpoint of improving sealing performance and flexibility, it is, for example, 0.1 to 50 μm, and preferably 1 to 20 μm.

[0136] In the display device 100, in order to enhance the effect of protecting the light emitting element 10 from moisture and oxygen in the atmosphere, it is preferable to further laminate an inorganic material film (barrier layer 24) on the above-mentioned resin layer. The inorganic material constituting the inorganic material film laminated on the resin layer and the formation method thereof are the same as those of the inorganic material film covering the above-mentioned light emitting element 10.

[0137] The thickness of the inorganic material film formed on the resin layer is not limited, but from the viewpoint of improving sealing performance, it is, for example, 0.01 to 10 μm, and preferably 0.1 to 5 μm.

[0138] In the display device 100, a barrier layer 24, a sealing layer 22, and a barrier layer 24 are provided in this order on the light-emitting element 10. Here, since the sealing layer 22 is composed of a resin layer obtained by curing the sealant in this embodiment having a high level of storage stability, a display device 100 with excellent reliability can be obtained. Specifically, even when a plasma treatment process is performed when forming the barrier layer 24 on the sealing layer 22, damage to the barrier layer 24 can be suppressed. In addition, since the resin layer itself constituting the sealing layer 22 is not easily deteriorated by the plasma treatment, damage to the light-emitting element 10 can be suppressed. EXAMPLES

[0139] EXAMPLES Hereinafter, the present invention will be described with reference to examples and comparative examples, but the present invention is not limited to these. First, the materials used in the following examples are listed. ((A) Cationic Polymerizable Compound) Polymerizable compound 1: alicyclic epoxy compound (4,4'-bis(1,2-epoxycyclohexane)), CEL8010, manufactured by Daicel Corporation (compound of the following formula (estimated))

[0140] [ka]

[0141] Polymerizable compound 2: oxetane compound, (3-ethyl-3{[(3-ethyloxetan-3-yl)methoxy]methyl}oxetane, OXT-221, manufactured by Toagosei Co., Ltd. Polymerizable compound 3: epoxy compound (glycidyl ether compound), 1,6-hexanediol diglycidyl ether, Epogosey HD (D), manufactured by Yokkaichi Synthetic Co., Ltd.

[0142] ((B) Cationic Polymerization Initiator) Polymerization initiator 1: Photocationic initiator, CPI-210S, manufactured by San-Apro Co., Ltd.

[0143] ((C) Leveling agent) Leveling agent 1: Polyester modified polydimethylsiloxane, BYK-310N (manufactured by BYK-Chemie) Leveling agent 2: Aralkyl-modified polymethylalkylsiloxane, BYK-323 (manufactured by BYK-Chemie) Leveling agent 3: reactive fluorine leveling agent, Viscoat 13F (Osaka Organic Chemical Industry Co., Ltd.) Leveling agent 4: Acrylic copolymer, BYK-350 (manufactured by BYK-Chemie) Leveling agent 5: Acrylic copolymer, Polyflow No. 90 (Kyoeisha) Leveling agent 6: Silicone-containing polymer, Polyflow KL-700 (Kyoeisha) Leveling agent 7: Fluorine-containing and lipophilic group-containing oligomer, F552 (DIC Corporation) (sensitizer) Sensitizer 1: Photocationic sensitizer (anthracene compound), UVS-1331 (Kawasaki Chemical Industries, Ltd.)

[0144] (Examples 1 to 10, Comparative Examples 1 and 2) The components were mixed to obtain the composition shown in Table 1, and a sealant was obtained as a liquid composition that did not contain a solvent. Specifically, the components listed in Table 1, except for the polymerization initiator, were mixed in a 19 mL glass container. Ultrasonic waves were applied to the glass container for 10 minutes, and then nitrogen bubbling was performed at 0.1 mL / min. The polymerization initiator in the amount shown in Table 1 was added to the obtained mixture and further mixed. The mixture was then stirred until no powdery matter was visible, and a sealant was obtained.

[0145] The physical properties of the sealant or its cured product obtained in each example were measured by the following methods. The measurement results are shown in Table 1.

[0146] (Droplet diameter ratio R) The droplet size ratio R was measured by each of the following steps (i) to (iv). The measurement was started within 3 hours after the production of the sealant obtained in each example. Step (i) After the sealant obtained in each example was cooled to 23°C, a portion of the sealant for display elements was sampled and introduced into an inkjet cartridge (DMC-11610, manufactured by Fujifilm Dimatix). After introduction, the temperature of the sealant was increased to 35°C by heating the cartridge. The sealant was kept at this temperature for 10 minutes. Next, the inkjet cartridge containing the sealant was set in an inkjet device (DMP-2831, manufactured by Fujifilm Dimatix), and the sealant was inkjet coated onto the SiN substrate under the following conditions. (a) Discharge volume: 7 picoliters (b) Temperature of SiN substrate and ambient temperature: 23°C The diameter of the sealant droplet was measured 180 seconds after it was applied by inkjet coating. The average value of the maximum and minimum diameters was taken, and the measurement result was designated as D1.

[0147] Step (ii) 9 to 11 g of the sealant for display elements kept at 23° C. in the step (i) was introduced into a glass container having a volume of 19 mL, and the container lid was tightly closed with a sealing tape and refrigerated for 7 days at 5° C. The upper space inside the container was left as air.

[0148] Step (iii) The sealant refrigerated in step (ii) was returned to 23° C., introduced into an inkjet cartridge, and kept at 35° C. for 10 minutes. Next, the inkjet cartridge containing the sealant was set in an inkjet device, and the sealant was inkjet coated onto the SiN substrate under the following conditions. (a) Discharge volume: 7 picoliters (b) Temperature of SiN substrate and ambient temperature: 23°C After 180 seconds had elapsed since the droplets had landed, the diameter of the droplets of the sealant for display elements was measured, and the average value of the maximum and minimum diameters was taken, and the measurement result was designated as D2. Step (iv) (iv) From the above D1 and D2, the droplet size ratio R=D2 / D1 was calculated.

[0149] (viscosity measurement) The viscosity of the curable composition obtained in each example was measured at 25° C. and 20 rpm using an E-type viscometer (LV DV-II+ Pro, manufactured by BROOKFIELD Corporation).

[0150] (thixotropy) The thixotropy (TI value) was determined by the following formula, using the same measuring device as used for viscosity measurement, and measuring the viscosity at 25° C. and at rotation speeds of 5 rpm and 50 rpm. TI value = (viscosity at 5 rpm) ÷ (viscosity at 50 rpm)

[0151] (Evaluation method) (Inkjet coating characteristics) Inkjet ejection properties were evaluated as inkjet coating characteristics in steps (i) and (iii) shown in the measurement method of the droplet size ratio R. The inkjet ejection device used was DMP-2831 manufactured by Fujifilm Dimatix, and inkjet coating was performed at a head temperature of 35°C and an applied voltage of 35V. The evaluation criteria are as follows. OK: The inkjet head was heated to 35°C, and the ink was stably applied from the inkjet device when ejected. NG: When the inkjet head was heated to 35°C and ejected, mist was generated or ejection was not achieved.

[0152] (Edge retention) (Production of evaluation samples) For the evaluation sample of edge retention, a laminate to be used as the evaluation sample was formed by the following procedure. That is, the sealant obtained in each example was introduced into an inkjet cartridge DMC-11610 (manufactured by Fujifilm Dimatix). The inkjet cartridge was set in an inkjet device DMP-2831 (manufactured by Fujifilm Dimatix), and after adjusting the discharge state, it was applied to alkali-free glass in a size of 20 mm wide x 20 mm long so that the thickness after curing would be 10 μm. The obtained coating film was left at room temperature (25° C.) for 3 minutes while purging with nitrogen, and then it was irradiated with a UV-LED with a wavelength of 395 nm at an illuminance of 1000 mW / cm. 2 , cumulative light intensity 1500mJ / cm 2 The mixture was cured with.

[0153] (Observation of Samples) The coating width of the resulting coating film was measured vertically and horizontally at three points using a stylus profiler, Alpha-Step D-600 (manufactured by ULVAC), the average value was calculated, and the coating width was evaluated according to the following criteria. NG: Coating width is 20.50mm or more OK: Coating width is less than 20.50 mm

[0154] [Table 1]

[0155] *The unit of viscosity in Table 1 is mPa·sec (millipascal second). *The unit of drop diameter in Table 1 is μm (microns).

[0156] As can be seen from Table 1, the sealant obtained in each Example contained a leveling agent and had a specific range of droplet size ratio R, and therefore had a high level of storage stability and high edge retention. Therefore, by using the sealant in each Example to seal an organic EL display element, an organic EL display device with excellent reliability can be obtained.

[0157] This application claims priority based on Japanese Patent Application No. 2021-080497, filed on May 11, 2021, the disclosure of which is incorporated herein in its entirety. [Explanation of symbols]

[0158] 10 Light emitting element 21 Barrier layer, touch panel layer or surface protection layer 22 Sealing layer, overcoat layer, or barrier layer 23 Planarization or sealing layer 24 Barrier layer 100 display device

Claims

1. The following components (A) to (C): (A) a cationically polymerizable compound, (B) a cationic polymerization initiator, (C) Leveling agent A sealant for a display element comprising: The droplet size ratio R of the sealant for a display element, which is measured by the following measurement procedure, is 0.5 or more and 1.1 or less, The viscosity at 25°C and 20 rpm measured with an E-type viscometer is 5 mPa·s or more and 80 mPa·s or less. A sealant for display elements (excluding a sealant for display elements containing 3-ethyl-3{[(3-ethyloxetan-3-yl)methoxy]methyl}oxetane, neopentyl glycol diglycidyl ether, a cationic polymerization initiator, an organic solvent having a contact angle with SiN of 1° or less, and a silicone-based leveling agent, and a sealant for display elements containing a linear monofunctional epoxy compound having 7 or more carbon atoms). [Measurement procedure] (i) After the display element sealant is kept at 23° C., a portion of the display element sealant is sampled and ink-jet coated onto a SiN substrate under the following conditions. (a) Discharge volume: 7 picoliters (b) Temperature of SiN substrate and atmospheric temperature: 23° C. After 180 seconds have elapsed since the droplet landed, the diameter of the droplet of the sealant for a display element is measured, and the measurement result is designated as D1. (ii) 9 to 11 g of the sealant for display elements kept at 23° C. in the step (i) is introduced into a glass container having a volume of 19 mL, and then the container lid is closed. The container containing the sealant for display elements is refrigerated at 5° C. for 7 days. (iii) The sealant for a display element refrigerated in the step (ii) is collected, and the sealant for a display element is ink-jet coated onto a SiN substrate under the following conditions. (a) Discharge volume: 7 picoliters (b) Temperature of SiN substrate and atmospheric temperature: 23° C. After 180 seconds have elapsed since the droplets landed, the diameter of the droplets of the sealant for a display element is measured, and the measurement result is designated as D2. (iv) The droplet size ratio R=D2 / D1 is calculated from D1 and D2.

2. The sealant for a display element according to claim 1 , The sealant for display elements, wherein the component (C) is at least one selected from the group consisting of silicone-based polymers and acrylate-based polymers.

3. The sealant for a display element according to claim 1 , The sealant for display elements, wherein the component (C) is a silicone-based polymer having a polymethylsiloxane structure or a polydimethylsiloxane structure in the molecule.

4. The sealant for a display element according to claim 1 , The sealant for a display element, wherein the component (C) is a polymer containing a structural unit derived from an alkyl (meth)acrylate ester.

5. The following components (A) to (C): (A) a cationically polymerizable compound, (B) a cationic polymerization initiator, (C) Leveling agent A sealant for a display element comprising: The droplet size ratio R of the sealant for a display element, which is measured by the following measurement procedure, is 0.5 or more and 1.1 or less, The viscosity at 25°C and 20 rpm measured with an E-type viscometer is 5 mPa s or more and 80 mPa s or less, A sealant for display elements, in which the component (C) is a silicone-based polymer having a polymethylsiloxane structure or a polydimethylsiloxane structure in the molecule (however, excluding a sealant for display elements containing 3-ethyl-3{[(3-ethyloxetan-3-yl)methoxy]methyl}oxetane, neopentyl glycol diglycidyl ether, a cationic polymerization initiator, an organic solvent having a contact angle with SiN of 1° or less, and a silicone-based leveling agent). [Measurement procedure] (i) After the display element sealant is kept at 23° C., a portion of the display element sealant is sampled and ink-jet coated onto a SiN substrate under the following conditions. (a) Discharge volume: 7 picoliters (b) Temperature of SiN substrate and atmospheric temperature: 23° C. After 180 seconds have elapsed since the droplet landed, the diameter of the droplet of the sealant for a display element is measured, and the measurement result is designated as D1. (ii) 9 to 11 g of the sealant for display elements kept at 23° C. in the step (i) is introduced into a glass container having a volume of 19 mL, and then the container lid is closed. The container containing the sealant for display elements is refrigerated at 5° C. for 7 days. (iii) The sealant for a display element refrigerated in the step (ii) is collected, and the sealant for a display element is ink-jet coated onto a SiN substrate under the following conditions. (a) Discharge volume: 7 picoliters (b) Temperature of SiN substrate and atmospheric temperature: 23° C. After 180 seconds have elapsed since the droplets landed, the diameter of the droplets of the sealant for a display element is measured, and the measurement result is designated as D2. (iv) The droplet size ratio R=D2 / D1 is calculated from D1 and D2.

6. The sealant for display elements according to any one of claims 1 to 5, The sealant for a display element, wherein the component (A) contains one or both of an epoxy compound and an oxetane compound.

7. The sealant for display elements according to any one of claims 1 to 5, The sealant for a display element, wherein the content of the component (C) is 0.01% by mass or more and 5% by mass or less with respect to 100% by mass of the component (A).

8. The sealant for display elements according to any one of claims 1 to 5, The sealant for display elements, wherein the component (B) is a photocationic polymerization initiator that generates a cationic species that initiates polymerization by the action of light.

9. The sealant for display elements according to any one of claims 1 to 5, A sealant for display elements, for sealing organic EL display elements.

10. A cured product obtained by curing the sealant for display elements according to any one of claims 1 to 5.

11. A substrate; A display element disposed on the substrate; A sealing layer that covers the display element; Including, A display device, wherein the sealing layer is formed from a cured product of the sealant for display elements according to any one of claims 1 to 5.

Citation Information

Patent Citations

  • Sealant for display elements, organic el element sealant, and cured product thereof

    JP2019203105A

  • Ultraviolet curable resin composition, method for manufacturing light-emitting device, and light-emitting device

    JP2020105482A

  • Ultraviolet curable resin composition, method for manufacturing light-emitting device, and light-emitting device

    JP2020105483A

  • Encapsulating composition

    KR1020200069757A

  • Sealant for organic electroluminescent display elements

    WO2015068454A1